1998
DOI: 10.1902/jop.1998.69.2.269
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Diseases in the United States Population

Abstract: Recent epidemiologic surveys and studies have provided important information on the prevalence, extent, and severity of periodontal diseases in the United States. Over 50% of adults had gingivitis on an average of 3 to 4 teeth. Subgingival calculus was present in 67% of the population. Adult periodontitis, measured by the presence of periodontal pockets > or = 4 mm, was found in about 30% of the population on an average of 3 to 4 teeth. Severe pockets > or = 6 mm were found in less than 5% of the population. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
279
2
19

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 348 publications
(311 citation statements)
references
References 48 publications
(11 reference statements)
11
279
2
19
Order By: Relevance
“…However, the role of gingivitis in periodontitis pathogenesis remains controversial: an etiological connection between them has been postulated but not yet proved. One confounding factor has been that not all gingivitis cases proceed into periodontitis: epidemiological studies showed that B50% of adults have gingivitis around more than six teeth (Oliver et al, 1998), while only 15% of adults suffer from periodontitis (Oliver et al, 1991). In our identified 'gingivitis-driver' genera, several species (for example, Tannerella forsythia, Peptostreptococcus micros (Parvimonas micra), Fusobacterium nucleatum subsp., Haemophilus paraphrophilus and Capnocytophaga sp.…”
Section: Discussionmentioning
confidence: 81%
“…However, the role of gingivitis in periodontitis pathogenesis remains controversial: an etiological connection between them has been postulated but not yet proved. One confounding factor has been that not all gingivitis cases proceed into periodontitis: epidemiological studies showed that B50% of adults have gingivitis around more than six teeth (Oliver et al, 1998), while only 15% of adults suffer from periodontitis (Oliver et al, 1991). In our identified 'gingivitis-driver' genera, several species (for example, Tannerella forsythia, Peptostreptococcus micros (Parvimonas micra), Fusobacterium nucleatum subsp., Haemophilus paraphrophilus and Capnocytophaga sp.…”
Section: Discussionmentioning
confidence: 81%
“…Only 1.4% of our population had loss of attachment of 3 mm or greater in 25% or over of sites, whereas one-third of the Alabama subjects had this level of disease. It has been reported that there is a high incidence of early-onset periodontitis amongst AfricanAmericans in certain regions of USA 30 and this may explain, in part, the higher prevalence of periodontal disease in the North Carolina and Alabama studies. Davenport et al 4 also gave some indication of the level of periodontal disease in their population: the control subjects had a mean probing depth of 3.85 mm and the case subjects had a mean probing depth of 3.72 mm.…”
Section: Discussionmentioning
confidence: 98%
“…19 -21 Periodontal disease is a chronic inflammatory disease of the periodontium that leads to erosion of the attachment apparatus and supporting bone for the teeth 22 and is one of the most common chronic infectious diseases of humans. 23 Porphyromonas gingivalis is the primary pathogenetic agent of adult periodontal disease. 24,25 Haraszthy et al 26 detected P gingivalis in human atheromatous tissue by polymerase chain reaction (PCR), indicating that P gingivalis gains access to the vasculature and localizes at sites of atheroma development.…”
mentioning
confidence: 99%